The Awenda “Council Rock”: Faking Anishinabe-Crown History on Granite - Benn, Carl (Ontario History)

(untitled) (The Ontario Historical Society, 2025)
There are engravings on a large rock in Awenda Provincial Park near southern Ontario’s Georgian Bay that suggest they date to the Penetanguishene Purchase of 1795. Thus, someone viewing the inscriptions might think they are significant in the history of Anishinabe-Crown relations. They are not. The engravings are deceitful modern fakes of no value for understanding Crown-Indigenous relations in the late 1700s. Sadly, people have accepted them as genuine. This has corrupted understanding of the region’s history and led Indigenous protesters to occupy the site under the false impression that the location is historically important because of the engravings. This article exposes the fraud, assesses its impact, considers issues of failing to evaluate our physical heritage accurately, and notes how falling victim to deceptions undermines efforts to achieve truth and reconciliation between Indigenous peoples and the broader Canadian population.